Implementation of Problem Based Learning Model to Improve Early Childhood Abilities in Creative Thinking - Pikir Wisnu Wijayanto; Nurpeni Priyatiningsih; Herman Herman; Sudadi Sudadi; Nanda Saputra (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The study below examines the development of students' critical and creative thinking abilities through the use of article reviews and the Problem Based Learning instructional approach. This study is qualitative and was conducted utilizing library research, specifically library research that used data grouping methods. It was then completed by examining and studying numerous pertinent research publications and papers. utilizing analytical methods for gathering, combining, and recognizing secondary data from numerous pertinent investigations. The adoption of the Problem Based Learning learning paradigm itself can boost students' capacity for creative thought, according to the study's findings. The findings of research done using library resources revealed that students' capacities for creative thought had improved, with outcomes moving into the medium category. In this study, four factors—fluency, flexibility, originality, and elaboration—were also linked to an improvement in students' capacity for creative thought. It follows that the application of the learning paradigm that Problem Based Learning is capable of improving students' creative thinking skills.